Writer in exile/writer in revolt critical perspectives on Carlos Bulosan - Cabusao, Jeffrey Arellano (Lanham, Maryland University Press of America, 2016)
This book gathers pioneering essays by major scholars as well as historic documents on Carlos Bulosan's work and life for the first time. This anthology provides the reader an opportunity to trace the development of a body of knowledge called Bulosan criticism within the United States and the Philippines.
I. Bulosan's voice: listening to the manong generation -- II. Location of exile: creating an alter/native Filipino literary prctice -- III. Writer as worker: broadening the Bulosan canon -- IV. Collective memory and revolt: becoming Filipino-becoming free.
Includes bibliographical references.
Keywords: Bulosan, Carlos -- Criticism and interpretation; Bulosan, Carlos -- Political and social views